The Effectiveness of Applications on Promoting the Growth and Development of Infants Born Prematurely after Discharge from the Hospital for Caregivers - Sritakaew, Nuttaya; Meesomsak, Nisapichayapak; Thohinung, Usa; Rojanaprasert, Pilailak (Journal of The Royal Thai Army Nurses, 2024)
This quasi-experimental research study investigates the effectiveness of a mobile application in promoting the growth and development of preterm infants after discharge from the hospital. The study utilized purposive sampling, comprising 30 caregivers of preterm infants, residing in Khlong Hok sub-district, Pathum Thani province, selected through specific and targeted criteria based on predetermined qualifications. The research tools used in the study are: 1) an application promoting the growth and developmental milestones of preterm infants after discharge from the hospital 2) a general information questionnaire for caregivers 3) a questionnaire to assess caregivers’ knowledge 4) a questionnaire to assess caregivers’ obstacles and 5) a satisfaction evaluation form for the application. Data were collected from October 2566 to February 2567, and the analysis involves both descriptive statistics and paired t-test statistics. The research findings revealed that there is a statistically significant difference in the average scores of knowledges and perception before and after the experiment at a significance level of .05. Additionally, caregivers express a high level of overall satisfaction with the application (M = 4.363, SD = .761) which indicates that the application effectively supports caregivers of preterm infants by increasing their knowledge and awareness of caregiving obstacles. It also helps improve the quality of care, promoting the growth and development of preterm infants upon returning home.